Desenvolvimento de uma metodologia, com base na teoria fuzzy, aplicada a modelos da demanda bioquímica de oxigênio (DBO) e oxigênio dissolvido (OD), para calcular o risco de degradação ambiental em rios naturais - Lopes, Ada Amélia Sanders (2009)
On the basis of the Principles of the Mass Transport, the mathematical model developed in this study establishes the relations between the Biochemical Oxygen Demand (BOD) and Dissolved Oxygen (DO), for different sources of launchings. The application of the fuzzy theory in this model of pollutant transport allows that the existing uncertainties in the variable involved in these processes, specifically in the solution of the advective diffusion equation, is able to evaluate the risks of contamination of a water system ahead of the pollutant substance launching. The fuzzy methodology was developed with the objective to transform the mathematical model of DBO/OD into a set of fuzzy differential equations, where the main parameters in this model had been represented as Membership functions. A computational program was developed for this study, codified in language FORTRAN 90, that allows us to construct models of simulation of water quality, on the basis of the methodology proposed. Some distinct scenes had been considered that describe the alterations in the quality of the water in natural rivers, on the basis of the investigation of the hydraulics parameters, in the formations of the membership functions of the concentration and in the propagation of a pollutant cloud. The results present the analyses of the risk of environmental degradation, and the analyses of the guarantee, that are influenced by the hydraulics and hydrologics parameters, standing out the outflows for any type of launching, the bed slope and the roughness. In synthesis, the fuzzy methodology is a tool of planning and management of water resources and, an alternative procedure when applied to the processes of pollutant transport